2022
DOI: 10.3390/microorganisms10010097
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Shift and Metabolic Adaptations during Leishmania Quiescence Using Stationary Phase and Drug Pressure as Models

Abstract: Microorganisms can adopt a quiescent physiological condition which acts as a survival strategy under unfavorable conditions. Quiescent cells are characterized by slow or non-proliferation and a deep downregulation of processes related to biosynthesis. Although quiescence has been described mostly in bacteria, this survival skill is widespread, including in eukaryotic microorganisms. In Leishmania, a digenetic parasitic protozoan that causes a major infectious disease, quiescence has been demonstrated, but the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 83 publications
1
23
0
Order By: Relevance
“…Secondly, in vitro, we showed that a strain of L. lainsoni entered in quiescence under stationary phase or antimony pressure. Several transcriptional signatures were shared by the parasites surviving to both environmental insults: among these, a series of transcripts were present in higher abundance, in a general background of transcriptional shift (Jara et al, 2022). These molecular similarities validated the quiescent character of Leishmania under antimony pressure.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…Secondly, in vitro, we showed that a strain of L. lainsoni entered in quiescence under stationary phase or antimony pressure. Several transcriptional signatures were shared by the parasites surviving to both environmental insults: among these, a series of transcripts were present in higher abundance, in a general background of transcriptional shift (Jara et al, 2022). These molecular similarities validated the quiescent character of Leishmania under antimony pressure.…”
Section: Introductionmentioning
confidence: 58%
“…Nine of them were selected for present study, according to the following inclusion criteria: (i) first episode of leishmaniasis, (ii) cutaneous form of the disease, (iii) no previous treatment before attending to the clinic, (iv) complete therapy with antimonial post-diagnosis, (v) no concomitant disease and (vi) infecting species typed as Leishmania braziliensis. One strain of Leishmania lainsoni was included in the study as control: this is a line highly susceptible to antimonials, for which the existence of quiescence after PAT exposure was demonstrated (Jara et al, 2022). For each isolate, enhanced green fluorescent protein (EGFP) was integrated within the 18S ribosomal DNA locus, further called rEGFP with the use of the pLEXSY-hyg system (Jena Bioscience) as previously reported elsewhere (Bolhassani et al, 2011;Jara et al, 2022).…”
Section: Parasitesmentioning
confidence: 99%
See 3 more Smart Citations